Teachers as agents of change: positive discipline for inclusive classrooms in Kakuma refugee camp. Issue 2 (28th January 2021) - Mendenhall, Mary; Cha, Jihae; Falk, Danielle; Bergin, Charlotte; Bowden, Lauren
ABSTRACT: Refugee children have often witnessed or experienced trauma, violence, and death. While conflict harms the psychosocial well-being and emotional development of children, an inclusive educational environment can serve as a safe haven for refugee students. Drawing on qualitative data collected between 2015–2017 in Kakuma refugee camp in Kenya, including 81 semi-structured interviews and extensive feedback gathered during teacher training workshops, this paper examines the micro-level disciplinary practices among teachers that promote or impede the inclusion of refugee children. The paper presents the tension between teachers' own negative experiences with corporal punishment as students, and their justification for using corporal punishment as teachers. Additionally, it highlights the role that continuous professional development plays in making positive changes to teachers' beliefs and practices. The authors argue that providing a safe space for reflection and discussion on corporal punishment and positive discipline is pertinent to reducing negative practices and stress the key role teachers play in creating such environments.